Hate Crimes and Legal Protections: Efficacy of Anti-Discrimination Laws (Journal of Advances and Scholarly Researches in Allied Education, 2020)
A crime perpetrated against an individual, their property, or society with the intent to harm them because of their race, religion, disability, sexual orientation, or ethnicity or national origin. Even though it lacks binding legal force, this term has widespread acceptance. It's usually aggressive, although there are more nuanced kinds as well. When someone is assaulted because to their membership in a certain group, this kind of crime takes place. This is common in many countries throughout the globe. And the same holds true for India. There are many different types of hate crimes committed in India, the most common of which are those based on religion or caste. Although mob lynching is not explicitly forbidden by law, it is against the law to use hate speech or to incite animosity between groups. Sections153, 153-A, 295-A, and 298 of the Indian Penal Code (IPC) contain the relevant legislation.